DESIGN OF MEASURING AND CONTROL FLOW RATE TOOL IN COAL PIPE STEAM POWER PLANT - Marcelino Fredianto, Rn.
The Electric Steam of Power Plant has 48% part out of all the electric generation in Indonesia, therefore it is a must to keep the plant performance in their best conditions. There are a lot of problems in a Power plant performance and one of the examples is to make sure the efficiency of combustion that is happened in a boiler. However, the problem above is not easy to solved and in fact the condition inside the boiler is difficult to observed. In this research, there will be done the balancing of coal flow rate of each coal pipe, with the result that the combustion will happened inside a boiler with tangential configuration by burner in each of the tip will produced fire ball exactly in the middle and is working in the best efficiency. The balancing process need an accurate fluid velocity data from each of the coal pipe, therefore in this research the writer will going to design and done the optimization of measuring tool and measuring system. In this research, the writer will also be looking for a solution from the blocking problem that happened to the measuring tool as a consequence of a low-quality condition of coal. Other than that, in this research will be done the designing of fluid flow rate regulator along with the control mechanism to fulfill the balancing process. In this research, there will be obtained two option for the sensors shape of annubar pilot tube, which are streamline and circular as a measuring sensors tool. The shape of streamline will give the better result of the energy loss section, whereas the shape of circular is simpler. The Purging System in this system will be used with the compressor component to transmit the compressed air to the port inside the sensor of measuring tool by the mechanism of timing opening solenoid valve. The fluid flow rate regulator that is going to be used is slide gate valve with a PLC controller and pneumatic actuator.